Case Report: A rare diffuse mitral valvular myxoma - Dou, Dongqing; Wu, Jun; Yuan, Wei; Wu, Haibo; Wang, Qimin (Frontiers in Cardiovascular Medicine, 2024)
Cardiac myxoma is a common benign tumor, however, myxoma extensively distributed on the mitral valve is rare and seldom reported. A patient who presented with exertional dyspnea and chest tightness was examined by transthoracic and transesophageal echocardiography successively. Multiple neoplasms on the mitral valve with moderate mitral regurgitation were found and were further proved to be a diffuse myxoma on the mitral valve by histology. Three-dimensional transesophageal echocardiography provided a precise evaluation of the mitral valve neoplasms, contributing to clinical decision-making.